Functionalized polyester-based materials as UV curable adhesives - Cernadas, T. (2021)
UV curable adhesives offer major advantages in comparison to other polymeric based adhesive systems, such as fast-curing rate and control of the polymerization heat evolution, being ideal for application on damaged tissues. Herein, functionalized polymers were prepared by modifying polycaprolactone diol (PCL) with an isocyanate-functional unsaturated acrylic ester, Laromer® 9000, using two different proportions. These functionalized materials were chemically/physically characterized and, after the addition of a biocompatible photoinitiator (Irgacure® 2959), were crosslinked by UV light irradiation. Such procedure allows the obtention of flexible transparent films. Films’ properties such as swelling, hydrolytic degradation, thermal stability, surface energy and adhesive capacity were evaluated. Furthermore, to assess the applicability of the films in biomedical applications, their haemocompatibility and biocompatibility were determined using human dermal fibroblasts as model.